Karla Flemming: capstone - Flemming, Karla, artist (Colorado State University. Libraries, 2016)
The artist's statement: Given our digital age and the plethora of issues facing our developing world, the need for the communication of compelling messages has never been stronger. Design has the ability to make the complex simple and draw emotive responses from viewers in extremely direct ways. Therefore, it is my intention to craft potent vehicles for the delivery of messages that will get through to people in an age where we are overloaded with information. This has led me to use a wide range of traditional and new media in my work. I believe that to fully engage viewers over a digital platform, it is important to spark interest and invite viewers to question the work's craft similar to how they would if they were seeing a piece in person. This has often led me to engage in very in-depth processes of prototype building, photography, or painting to produce my finished designs.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design